Assessing the efficacy of modified Marshall scoring system in severity assessment of acute pancreatitis in comparison to Ranson score at tertiary centre - Vashistha, Aakansha; Khandelwal, Radha Govind; Om, Prabha; Rundla, Manish (International Surgery Journal, 2023)
Background: Early determination of severity of acute pancreatitis is essential for prediction of prognosis and proper treatment selection. This study aims to evaluate the effectiveness of the Modified Marshall scoring system in evaluating severity in acute pancreatitis at admission. Methods: A hospital based prospective observational study was conducted at SMS medical college, Jaipur from May 2019 to September 2021 with a sample size of 60 patients. Modified Marshall Score and Ranson’s score were done at admission and 48 hours respectively for same patient. Results: Most patients (31.66%) were among age group 31-45 years (mean age 43.95±16.28 years) with slight female (51.55%) preponderance. The mean hospital stay was 4.883±3.405 days with maximum mortality in first week (6/8). All patients with mild pancreatitis under Modified Marshall score were discharged uneventfully while patients with severe pancreatitis, 8 (25%) died. Respiratory system failure (48.33%) was most commonly involved followed by renal (16.66%) and cardiovascular system (11.66%). Single organ failure (35%) had no mortality while 2/3 patients with all three-organ system failure died. The AUC value of ROC curve (0.863) (p<0.001) showed that Modified Marshall score is a significant predictor for severity of acute pancreatitis. The correlation coefficient was strongly positive and statistically significant (p<0.001) for the relationship between Ranson’s score, Modified Marshall score and hospital stay. Conclusions: Modified Marshall Score is simple and equally effective tool for predicting severity and prognosis early in the course of disease. Therefore, it prevents delay in aggressive treatment of critically ill patient and would contribute to decrease mortality.